A Robust SMO-PLL Estimation Algorithm for Enhancing Rotor Position Accuracy and Reducing Chattering Issues in Sensorless FOC of SPMSM - Nektar Cahayasabda; Sekhul Ishak; Danang Suryo Wibowo; Aulia Rahmah Salsabila; Syifa Fajry Az Zahra; Isyatul Hani’ah; Khoirudin Fathoni; Mario Norman Syah (National Research and Innovation Agency, 2025)
Recent advancements in sensorless Field-oriented Control (FOC) of Surface Permanent Magnet Synchronous Motors (SPMSMs) have improved system reliability and cost-effectiveness. However, limitations such as speed chattering and inaccurate rotor position estimation remain problematic for Electric Vehicle (EV) applications. This study developed a sliding mode observer-phase locked loop (SMO-PLL) algorithm applied to sensorless FOC in SPMSMs. The SMO predicts the back EMF of the SPMSM, which the PLL then uses for precise rotor position and speed estimation. Simulations conducted in MATLAB Simulink demonstrate that the SMO-PLL significantly reduces chattering and achieves a rotor position estimation error of only 1 rad/min. While the quantitative integral error criteria for SMO-PLL (IAE: 0.0868, ITAE: 0.3069, ISE: 0.0229, ITSE: 0.0834) are slightly higher than those of Field Observer (FO) and Extended Electromagnetic Field Observer (EEMFO), speed control analysis confirms that SMO-PLL delivers a rapid steady-state response with minimal overshoot and oscillation. These findings are crucial for applications where speed stability is essential for passenger comfort and safety, highlighting the SMO-PLL's potential as a robust sensorless control solution for future EVs.